1985
DOI: 10.1159/000281023
|View full text |Cite
|
Sign up to set email alerts
|

Ureaplasmal Infections of the Male Urogenital Tract, in Particular Prostatitis, and Semen Quality

Abstract: Ureaplasma urealyticum is considered an etiologic agent in urogenital tract infections, especially prostatitis. Using the ‘four-specimen technique’, diagnosis can be based upon significant numbers of these microorganisms. In ejaculate, the critical number seems to be 103 cfu/ml of semen to discriminate between real infection and contamination during urethral passage. In our study, 46 of 412 samples (11.2%) exceeded this critical number. Most but not all patients suffering from ureaplasma-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
5

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 10 publications
2
19
0
5
Order By: Relevance
“…These results agree with the findings of Weidner et al [19], which failed to demonstrate any improvement of sperm quality in a group of men with chronic prostatitis. Our study of 60 men in which semen culture was positive showed no differences between antibiotic treatments and placebo with any improvement in sperm quality.…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with the findings of Weidner et al [19], which failed to demonstrate any improvement of sperm quality in a group of men with chronic prostatitis. Our study of 60 men in which semen culture was positive showed no differences between antibiotic treatments and placebo with any improvement in sperm quality.…”
Section: Discussionsupporting
confidence: 93%
“…Using the Four Glass technique, a comparison of the WBC concentration in the different samples could be helpful. Thus, a high concentration of WBC in VB3 supports the diagnosis of prostatitis, provided that VB2 is free of WBC [87].…”
Section: Leukocytospermia-an Indicator Of Male Reproductive Tract Infmentioning
confidence: 88%
“…Subfertil ve infertil erkeklerde subklinik genital trakt enfeksiyonlarının araştırıldığı çalışmalarda, semende UU ve MH görülme sıklığı, özellikle UU sıklığı anlamlı olarak yüksek bulunmuştur [9,10,11]. Weidner ve arkadaşları prostatitli olguların semen örneklerinde % 11,2 oranında UU izole ettiklerini bildirirken [12]; Salari ve arkadaşlarının üretritli olgular üzerinde yaptığı çalışmada ise UU sıklığının % 19,2 olduğu bildirilmiştir. Salari ve arkadaşlarının bu çalışmalarında, MG % 7,2, MH % 2,4 oranında izole edilerek, kültür pozitifliğinin UU ve MG için anlamlı olduğu ve bu iki ajanın non gonokoksik üretrite sebep olduğu belirtilmiştir [13] .…”
Section: Discussionunclassified
“…Lökospermi, 400'lük büyütme ile her mikroskop sahasında 5'ten fazla lökosit veya lökosit benzeri hücre görülmesi olarak tanım-lanır. İnfertil erkeklerin semen örneklerinde yüksek yoğunlukta lökosit bulunduğu ileri sürülmektedir [3,12]. Ancak kültür pozitif ve negatif olgularda lökospermi sıklığıyla ilgili net bir bilgi yoktur.…”
Section: Discussionunclassified
See 1 more Smart Citation